2023
DOI: 10.3390/su15118479
|View full text |Cite
|
Sign up to set email alerts
|

Agrochemical Input Behavior and Cleaner Production Adoption Willingness of Farmers in Beijing–Tianjin–Hebei, China

Abstract: Beijing–Tianjin–Hebei is an important agricultural production area in China, and farmers’ agrochemical input behavior directly affects the risk of agricultural non-point source pollution and the effect of green agricultural development. Based on a questionnaire survey and field interview data, this study investigated the agrochemical input behavior of farmers in Beijing–Tianjin–Hebei, and analyzed its influencing factors. Using the Probit model, we carried out an empirical study on farmers’ willingness to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Hypothesis H8 is confirmed. Previous studies have shown that government propaganda has a significant promoting effect on the willingness and behavior of farmers to participate [38,48]. Government propaganda, on the one hand, boosts the confidence of farmers in the forest ticket system.…”
Section: Government Propagandamentioning
confidence: 99%
“…Hypothesis H8 is confirmed. Previous studies have shown that government propaganda has a significant promoting effect on the willingness and behavior of farmers to participate [38,48]. Government propaganda, on the one hand, boosts the confidence of farmers in the forest ticket system.…”
Section: Government Propagandamentioning
confidence: 99%